2002
DOI: 10.1002/jemt.10015
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary neurotrophic factor increases the survival of magnocellular vasopressin and oxytocin neurons in rat supraoptic nucleus in organotypic cultures†

Abstract: Organotypic cultures of the rat hypothalamus are very useful models for the long-term study of parvocellular vasopressin (VP) neurons in the paraventricular (PVN) and suprachiasmatic (SCN) nuclei. However, they do not preserve significant numbers of VP magnocellular neurons (VP-MCNs) in either the PVN or the supraoptic nucleus (SON). Vutskits et al. [(1998) Neuroscience 87:571-582] reported that ciliary neurotrophic factor (CNTF) was a selective survival factor for rat VP-MCNs in organotypic cultures of the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…These immunoreactive neurons are similar in their morphological appearances to MCNs found in the SON in vivo (Armstrong, 1995). Although the MCN phenotypes are present in these cultures, it has also been shown that there is substantial programmed cell death of the MCN cell population in these slices (Vutskits et al, 1998;Rusnak et al, 2002Rusnak et al, , 2003. This is presumably because of the extensive axotomy that these neurons undergo during preparation of the slices.…”
Section: The In Vitro Modelsupporting
confidence: 60%
See 4 more Smart Citations
“…These immunoreactive neurons are similar in their morphological appearances to MCNs found in the SON in vivo (Armstrong, 1995). Although the MCN phenotypes are present in these cultures, it has also been shown that there is substantial programmed cell death of the MCN cell population in these slices (Vutskits et al, 1998;Rusnak et al, 2002Rusnak et al, , 2003. This is presumably because of the extensive axotomy that these neurons undergo during preparation of the slices.…”
Section: The In Vitro Modelsupporting
confidence: 60%
“…Consistent with the "neurotrophic hypothesis," which posits that the survival of neurons depends on the continuous retrograde supply of trophic factors from target organs (Purves, 1988;Oppenheim, 1989Oppenheim, , 1991, Vutskits et al (1998) proposed that the programmed cell death of MCNs in the HNS is attributable to the loss of specific trophic actors, presumably CNTF, from the neurohypophysis. In this regard, the rescue of the MCNs in vitro by CNTF (Vutskits et al, 1998;Rusnak et al, 2002Rusnak et al, , 2003 and the reversal of the TTX effect (Fig. 8) provide support for this proposal.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations